Rozwój sądownictwa w sprawach o zbrodnie stanu w przedrozbiorowej Polsce - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The author analyses the establishment and development of the Sejm Court (Parliamentary Court) over the several centuries of its history, and illustrates its final (in pre-partition Poland) legal form as the highest jurisdiction in cases of high treason, leaving aside the constitution of the Grodno Sejm of 1793, as it contributes little to the matter in question.When describing the history of the Sejm Court, presenting suggestions and opinions, and formulating them almost exclusively on the basis of the sources contained in Volumina Legum, the author seeks to describe the evolution of this jurisdiction from the times when it was merely the royal court to the period when it became a professional tribunal ruling in cases of high treason. He also refers to selected literature on the subject and other sources, but only to a limited extent. To demonstrate the evolution of one of the most important judicial institution in pre-partition Poland was the main inspiration for the author in tackling the subject and presenting his final conclusions.
Keywords: system sądowniczy; Polska przedrozbiorowa; zdrada stanu; Trybunał Koronny